Pertobatan dan Kemurtadan dalam Ibrani 4:4-6: Sebuah Analisis Biblikal - Tengker, Garry Robert; Kansil, Dicky (Pusat Studi Pentakosta Indonesia, 2024)
Repentance is a central theme in the Christian faith, and Hebrews 4:4-6 provides a serious warning about the possibility of someone who has experienced enlightenment and salvation to